2018
DOI: 10.2139/ssrn.3133344
|View full text |Cite
|
Sign up to set email alerts
|

Concentration in US Labor Markets: Evidence from Online Vacancy Data

Abstract: Steinbaum acknowledges the support of the Ewing Marion Kauffman Foundation. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 0 publications
4
70
0
Order By: Relevance
“…Bunting (1962, Appendix 16) finds a positive relationship between wages and concentration. A presumably incomplete list of recent papers includes: Azar, Marinescu, and Steinbaum (2017), Azar et al (2018), Benmelech, Bergman, and Kim (2018), Hershbein, Macaluso, and Yeh (2018), Lipsius (2018), Qui and Sojourner (2019), Rinz (2018), and Schubert, Stansbury, and Taska (2019).…”
Section: Wage-concentration Regressions In the Modelmentioning
confidence: 99%
“…Bunting (1962, Appendix 16) finds a positive relationship between wages and concentration. A presumably incomplete list of recent papers includes: Azar, Marinescu, and Steinbaum (2017), Azar et al (2018), Benmelech, Bergman, and Kim (2018), Hershbein, Macaluso, and Yeh (2018), Lipsius (2018), Qui and Sojourner (2019), Rinz (2018), and Schubert, Stansbury, and Taska (2019).…”
Section: Wage-concentration Regressions In the Modelmentioning
confidence: 99%
“…Deming and Kahn (2017) use job vacancy descriptions that have been processed into keywords to define general skills that have explanatory power for both pay and firm performance beyond the usual labour market classifications. Azar et al (2018) leverage online job vacancies, with job title text cleaned and standardised, to estimate the labour market concentration according to the Herfindahl-Hirchsman index.…”
Section: Literaturementioning
confidence: 99%
“…However, wages are also dependent on the labor market concentration and buyer-supplier relationships. In this regard, recent work on labor market monopsony and large-scale buyers showed that labor market concentration can reduce wages within certain type of occupations and industries (Azar et al, 2017(Azar et al, , 2018Wilmers, 2018;Rinz, 2018). This implies also that wages are partially determined by the industry and related labor market within that industry.…”
Section: Literature On Occupations Industries and Social Stratificationmentioning
confidence: 99%